UKRAINE AND POLAND: FACING THE 21ST CENTURY CHALLENGES - Igor Tsependa (Vasyl Stefanyk Precarpathian National University, 2015)
Establishing a common strategic framework is a decisive factor in the Ukrainian-Polish relations in the current social and political context. The complexity of the partnership between the two states arise from their geographical location on the borderline between civilizations, the site of historical cataclysms. At the same time, national sovereignty of was always a high priority for both peoples. The recognition of Ukraine's independence by Poland marked a new stage of rapprochement between Warsaw and Kyiv, the act being evidence of maturity of the Polish political elite. Poland made its best to promote the interest of Ukraine in the international political arena. The article suggests periodization in the history of the Ukrainian-Polish partnership. Ukrainian policy can be modelled on Poland's experience of the transformation of society. Being a member of the European Union, Poland advocates the idea of European and Euro-Atlantic integration of Ukraine. Increased economic cooperation is one of the aspects of the Ukrainian-Polish partnership. Cooperation at regional level, between local government bodies is also important for the relations between the two states. Step by step, visa regulations are being liberalized, interpersonal contacts broadened. The beginning of the 21st century witnesses a change in political consciousness of Ukrainian and Polish people, who reconsider painful events from their past.